Handbook of research on digital crime, cyberspace security, and information assurance - Cruz-Cunha, Maria Manuela, 1964-; Portela, Irene Maria, 1965-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This book combines the most recent developments in data protection and information communication technology (ICT) law with research surrounding current criminal behaviors in the digital sphere"--Provided by publisher.
Cybercrimes examples, risks, and threats -- Cyber security approaches and developments -- Legal aspects and ICT law -- Case studies.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 10/09/2014).
Keywords: Computer crimes; Computer security; Computer networks -- Security measures; Data protection; Information technology; Data privacy; ICT law; Information leakage; Internet security; Organizational privacy; Security regulation; Surveillance techniques; Virtual risks; Electronic books